Experimental study of thermal and airtightness performance of structural insulated panel joints in cold climates. (April 2017) - Kayello, Ahmad; Ge, Hua; Athienitis, Andreas; Rao, Jiwu
Abstract: The extreme climate and limited nature of local resources in the arctic create serious challenges for the many Inuit communities. Homelessness and housing shortages are still common, underlining the need for the construction of durable, sustainable, and affordable housing. The building envelope is highly susceptible to moisture damage and deterioration if not well designed and constructed, especially in the arctic. For this project, the thermal and airtightness performance of structural insulated panel (SIP) joints are studied. A full-scale test hut built with SIPs was constructed and tested in an environmental chamber at −20 °C and −40 °C, simulating arctic conditions. Eight types of SIP joints were monitored with thermocouples, with at least 6 thermocouples per joint. The SIPs were subjected to temperature differences of up to 62 °C and pressure differences up to 15 Pa. It is found that joints connecting three envelope elements are leakier and more susceptible to moisture damage than those connecting two. Though all joints are dependent on the tape seal to maintain airtightness, it is more difficult to ensure good air seal for the more complex joints. All the joints can be improved to be less dependent on the tape, though the joints most susceptible to moisture damage and mold growth are the top joints since moist indoor air tends to exfiltrate at those locations due to stack effect. Highlights: Full-scale testing of thermal and airtightness performance of SIP joints under cold temperatures in environmental chamber. Effect of air sealing and pressurization on SIP joints assessed with joint temperature profile measurements and simulations. Joints with two envelope elements demonstrated more consistent performance. Joints with three envelope elements have greater risk of air leakage, tape sealing these joints unreliable. Top joints are most susceptible to air exfiltration and moisture damage, improvement of joint design required.